Anesthetic Management of Children and Adolescents With Giant Axonal Neuropathy: A Large Case Series. Issue 10 (25th October 2021) - Yousef, Muhammad; Bharucha-Goebel, Diana; Saade, Dimah; Averion, Gilberto; Bönnemann, Carsten G.; Quezado, Zenaide M. N.
Abstract : Supplemental Digital Content is available in the text. Abstract : Giant axonal neuropathy (GAN) is a rare autosomal recessive neurodegenerative disorder caused by mutations in the GAN gene, which encodes for gigaxonin, a protein involved in intermediate filament processing in neural cells and fibroblasts. We report on 14 GAN patients who underwent 77 anesthetics during the conduct of an intrathecal gene transfer clinical trial from April 2015 to August 2020. We observed only a few nonsignificant perianesthetic complications. Our data expand the knowledge regarding safety of anesthesia for patients with this rare and potentially fatal disease and highlights the tolerability of shorter procedural sedation and anesthesia.